PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS NILAI AL-QURAN DAN HADITS UNTUK PENDIDIKAN ISLAM MODERN - Nadia Nabila; Zainal Mustofa; Hubir Hubir; Abdurrahman Abdurrahman (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
The educational paradigm has been profoundly transformed by technological advancement, including Islamic education. One of the greatest challenges is how to adapt learning media to align with technological progress while preserving the moral values that form the foundation of Islamic education. The purpose of this study is to develop ideas for learning media based on the values of the Qur’an and Hadith that can integrate the moral, spiritual, and cognitive elements of students. Using a descriptive qualitative approach, this research focuses on the values and concepts derived from the Qur’an and Hadith, as well as their relationship to the design of contemporary learning media. Data were collected through literature review and relevant journal research. The results of the study show that Islamic educational values such as knowledge (Iqra’), compassion (Rahmah), patience (Sabr), the exemplary behavior of the Prophet Muhammad (Uswah Hasanah), and effective communication have a significant influence on shaping Islamic-based learning media. The stages of media development—including needs analysis, design, development, implementation, and evaluation — systematically ensure the integration between academic information and religious principles. To make learning not only informative but also transformative, media design must integrate cognitive and spiritual values. Comprehensive Islamic education aims to enlighten the mind and nurture noble character by balancing intellectual and moral aspects. Therefore, the development of learning media based on the values of the Qur’an and Hadith is expected to become an innovative solution for contemporary Islamic education. It will harmonize technological progress with spirituality, making learning a means of attaining blessings and devotion to Allah SWT.